The Study of Mathematical Reasoning Using Cooperative Learning Among Grade 9 Students Darasamut Phuket School - เขาทอง ณัทฐินา; จิรวัตรพาณิช อนุวัตร; อึ๋งสืบเชื้อ ภานุพงษ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to study mathematical reasoning, academic achievement, and study the learners’ participation behavior, enthusiasm, and responsibility while learning through cooperative learning on the topic of probability of Mathayom 3 students. By using collaborative learning management, the samples was 27 Mathayom 3 students, using specific selection. The research tools consisted of 1) 6 mathematics learning management plans on probability. 2) Pre- and post-test on probability 3) Mathematical reasoning measurement and assessment form 4) Group work participation behavior observation form. Data were collected in the second semester of the academic year 2024. The research data included pre- and post-test data, mathematical reasoning assessment data, and participation behavior observation data. Data analysis used basic statistics, including mean, standard deviation, and content analysis. The research results found of mathematical reasoning on probability through collaborative learning of Mathayom 3 students. The target group of students had results in mathematical reasoning on the topic of probability through collaborative learning management for Mathayom 3 students. It was found that the students’ mathematical reasoning results were at a good level. Which is in line with the predicted assumptions. Academic achievement through collaborative learning on probability of Mathayom 3 students found that 27 students in the target group passed the academic achievement test. The learning achievement before studying probability had a mean of 7.2 and a standard deviation of 2.19. The learning achievement after studying probability had a mean of 15.89 and a standard deviation of 1.89 and the results of the evaluation of the participation behavior, enthusiasm and responsibility of the students through cooperative learning on the topic of probability of Mathayom 3 students It was found that the target group of students had participation, enthusiasm, and responsibility behaviors that passed the specified criteria, with an average score of 11.51 points, which was at a good level, passing the specified criteria. The highest average score was responsibility for assigned work, with an average score of 2.85 Next is work success, with an average score of 2.81. Next is participation in expressing opinions, with an average score of 2.78. Finally, work planning, with an average score of 2.63 From the above statistics, it can be seen that cooperative learning has a positive effect on students’ mathematical reasoning skills and positive learning behavior.